2008
DOI: 10.1111/j.1742-4658.2008.06399.x
|View full text |Cite
|
Sign up to set email alerts
|

Collective behavior in gene regulation: The cell is an oscillator, the cell cycle a developmental process

Abstract: The finding of a genome-wide oscillation in transcription that gates cells into S phase and coordinates mitochondrial and metabolic functions has altered our understanding of how the cell cycle is timed and how stable cellular phenotypes are maintained. Here we present the evidence and arguments in support of the idea that everything oscillates, and the rationale for viewing the cell as an attractor from which deterministic noise can be tuned by appropriate coupling among the many feedback loops, or regulons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 42 publications
(105 reference statements)
1
30
0
Order By: Relevance
“…Instead, they seem to extend into every domain of neural and behavioral functioning. The entire genome appears to be dynamic and show cycles of activity (Klevecz, Li, Marcus, & Frankel, 2008). For those who have devoted a career to the study of development, this all makes good sense.…”
Section: Bi-directional Features Of Nervous System Functioningmentioning
confidence: 99%
“…Instead, they seem to extend into every domain of neural and behavioral functioning. The entire genome appears to be dynamic and show cycles of activity (Klevecz, Li, Marcus, & Frankel, 2008). For those who have devoted a career to the study of development, this all makes good sense.…”
Section: Bi-directional Features Of Nervous System Functioningmentioning
confidence: 99%
“…It is the temporal variation in the GRF outputs that ultimately defines cell size, cell cycle frequency or status, developmental cell-fate decisions [15], the production of biomolecules such as mRNA [16], and the release of species such as Ca 2+ [17]. The form of the GRF output varies among biological systems and they may appear as a steady function, a gradual change, on–off switching [15, 18], bursts [19], oscillations [20, 21], or circadian clocks [22, 23]. Therefore, the noise associated with each GRF output is similarly time-dependent.…”
Section: Defining Biological Noisementioning
confidence: 99%
“…This phenomenon is observed in a wide range of scales and can be found, for example, in the arrhythmia of cardiac functions4, or in the firing of neurons56, where it has been tentatively explained on the basis of the well know bifurcation to chaos paradigm910, or in the distribution of population growth in yeast12, where it was ascribed to genetic regulatory circuits. Period doubling has also been observed during cell divisions and circadian cycles, where it can manifest spontaneously11 or in response to chemical perturbations13. Similarly, it has been shown that the genome-wide transcriptional oscillation in yeast can experience period doubling in reaction to drugs14.…”
mentioning
confidence: 97%